Comparison between apo and complexed structures of bothropstoxin-I reveals the role of Lys122 and Ca2+-binding loop region for the catalytically inactive Lys49-PLA(2)s - Fernandes, Carlos A. H. [UNESP]; Marchi-Salvador, Daniela P. [UNESP]; Salvador, Guilherme M. [UNESP]; Silva, Mabel C. O. [UNESP]; Costa, Tassia R.; Soares, Andreimar M.; Fontes, Marcos R. M. [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
Phospholipases A(2) (Asp49-PLA(2)s) are enzymes responsible for cellular membrane disruption through Ca2+-dependent hydrolysis of phospholipids. A class of these proteins (Lys49-PLA(2)s) does not show catalytic activity but can exert a pronounced local myotoxic effect that is not neutralized by serum therapy. In this work, we present five structures of Lys49-PLA(2)s from snakes of the Bothrops genus in apo form, complexed with PEG molecules and chemically modified by p-bromofenacil bromide (BPB), a classic inhibitor of PLA(2). We present herein an extensive structural analysis including: (i) the function of hydrophobic long-chain molecules as Lys49-PLA(2)s inhibitors, (ii) the role of Lys122, previously indicated as being responsible for Lys49-PLA(2)s catalytic inactivity and, (iii) a structural comparison of the Ca2+-binding loop region between Lys49 and Asp49-PLA(2)s. The Lys122 analysis of 30 different monomers for apo and complexed Lys49-PLA(2)s structures shows that this residue is very flexible and may bind to different carboxyl groups giving stability to the crystal structures. The structural comparisons of the Ca2+-binding loop region between Lys49 and Asp49-PLA(2)s reveal the importance of the Tyr28 residue conservation in Asp49-PLA(2)s to the integrity of this loop. The Tyr28 residue stabilizes this region by an interaction with Gly35 residue. In Lys49-PLA(2)s and low-catalytic Asp49-PLA(2)s this interaction does not occur, preventing the binding of Ca2+. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Phospholipase A(2); Myotoxicity; Homologue phospholipase A(2) (Lys49-PLA(2)s); Ca2+-binding loop; X-ray crystallography